Knowledge attitude and practice of paediatricians regarding tuberculosis case management in five major districts of Punjab state, India - Singh, Harmeet Pal; Bains, Harmesh S.; Dhooria, Gurdeep Singh; Pooni, Puneet A.; Bhat, Deepak (International Journal of Contemporary Pediatrics, 2020)
Background: The operational research was done to assess the Knowledge, Attitude and Practice regarding TB case management of Pediatricians. Place were five major cities of Punjab state, India. i.e. Ludhiana, Jalandhar, Amritsar, Patiala and Bathinda. Methods: Study design was observational cross-sectional study. Period was one year. The data collection was done from Paediatricians from 5 cities inhabiting approximately half of the urban population of Punjab, using a pre-tested, structured questionnaire and knowledge of TB and its management was assessed. Results: Total of 139 pediatricians participated in the study, 69% were male. Majority pediatricians had adequate knowledge of TB disease and case suspicion. Adequate knowledge of TB diagnosis was seen in 87% doctors. Only 20% doctors had adequate knowledge about treatment of TB cases. Overall 64% of Pediatricians referred TB cases to DOTS centre for treatment. Conclusions: Improving the treatment knowledge of paediatricians can go a long way in improving management of TB cases.